Blue Mining: Advancing Circular Economy Practices in Mining for Sustainability and Resource Efficiency - SME Annual Meeting 2025 - Angela Binder; Mareike Schubert; Yichen Jiang; Oliver Langefeld; Sandra Nowosad (Society for Mining, Metallurgy & Exploration, 2025)
GermanyINTRODUCTIONThe mining industry is currently characterized by various factors such as environmental impact, resource scarcity, social responsibility and geopolitical uncertainty. The production of minerals required to meet the demand for renewable energy is expected to increase by 500 % by 2050, particularly for critical minerals such as graphite, lithium and cobalt 1. Easily accessible deposits are often depleted, meaning that deeper and more complex deposits need to be developed. Furthermore, investors’ value systems have shifted towards more sustainable practices. Alternative approaches to solving this problem are therefore currently being developed, such as the Modular Mining Systems concept for scalable and adaptable mining projects 2. Many mining companies have also taken important steps to become more sustainable, implementing measures such as proactive closure strategies, restoration programs and the development of renewable energy projects. In the European Union, laws such as the Critical Raw Materials Act and the Net Zero Industry Act support the mining industry 3,4. They see it as important for the energy transition and promote more sustainable ways of working in the industry Particularly negative environmental impacts such as land degradation, scarcity of local water resources, water pollution and greenhouse gas emissions are ingrained in society’s memory. Despite these efforts, the public image has not yet changed. To change this perception, the industry must strive to better communicate its sustainable practices and the steps it is taking towards a more responsible and sustainable future, promote transparency and build trust.Digitalization, automation and electrification are driving the digital transformation in mining. However, their implementation can lead to higher capital expenditure, limiting their adoption across the industry. Furthermore, implementing new technologies can be a daunting task for any organization. Change management comes into play when introducing such disruptive technologies. It involves preparing an organization for change, potential resistance and establishing effective communication. This helps to ensure that the implementation is successful and the benefits of the new technology are maximized. Digital transformation requires well-trained, young mining, electrical, mechatronic and software engineers with a deep understanding of information systems. Unfortunately, the industry faces the enormous challenge of attracting this younger generation, who have little interest in the extraction of raw materials. The need for action is compounded by an aging active workforce heading into retirement and the forecast of increasing demand for critical minerals.In this challenging environment, the concept of Blue Mining with its constant further developments represents a promising approach. This implies a shift from a linear to a sustainably oriented circular economy. For the mining industry, this specifically means the introduction of innovative technologies, the increased recovery of materials from waste and the consistent questioning and application of circular principles along the entire life cycle of a mine. Such a change can not only reduce the environmental impact, but also contribute to economic resilience and increased social acceptance of mining.